Risk factors for breast cancer recurrence in postmenopausal women: a bibliometric study - Hoinoiu, Teodora; Piţ, Daniel; Oprean, Cristina; Hoinoiu, Bogdan; Diaconescu, Andra; Grujic, Ljubisa; Luca, Magda Mihaela; Grujic, Daciana (Frontiers in Oncology, 2025)
Breast cancer is a significant healthcare challenge, and despite advancements in treatment, the risk of recurrence remains a critical concern, particularly for postmenopausal women. Understanding the factors that contribute to this risk is essential for improving monitoring and prevention strategies, ultimately enhancing long-term care and disease management for this patient population. The study analyzes scholarly literature on recurrence patterns in postmenopausal Caucasian women with prior breast cancer, highlighting the potential for innovative insights to reduce breast cancer mortality and improve long-term survival. We used R software and the “R-Bibliometrix” package to analyze postmenopausal breast cancer recurrence. Data was collected from the Web of Science Core Collection database to identify relevant documents and highlight significant collaborative efforts and commonly used terminology. The extensive analysis included 500 articles authored by 3,204 individuals from 195 distinct sources, all published between 2010 and 2024. It specifically focused on assessing the risk of breast cancer recurrence in postmenopausal women. The results underscored several critical factors influencing the risk of recurrence, encompassing hormonal factors, lifestyle influences, the effectiveness of various types of adjuvant therapy, and the role of genetic factors. In conclusion, the research highlights the multifaceted nature of factors contributing to breast cancer recurrence in postmenopausal women. We believe that this study not only enhances the current understanding of the risk of breast cancer recurrence in postmenopausal women but also provides clear directions for future research and improvements in clinical practice and health policy.